Amorphous intergranular films act as ultra-efficient point defect sinks during collision cascades. (1st January 2016) - Ludy, Joseph E.; Rupert, Timothy J.
Graphical abstract: Abstract: Atomistic simulations are used to explore the effect of interfacial structure on residual radiation damage. Specifically, an ordered grain boundary is compared to a disordered amorphous intergranular film, to investigate how interface thickness and free volume impacts point defect recombination. Collision cascades are simulated and residual point defect populations are analyzed as a function of boundary type and primary knock on atom energy. While ordered grain boundaries easily absorb interstitials, these interfaces are inefficient vacancy sinks. Alternatively, amorphous intergranular films act as ultra-efficient, unbiased defect sinks, providing a path for the creation of radiation-tolerant materials.